2022
DOI: 10.1364/prj.467695
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared single-photon upconversion spectroscopy based on temporal-spectral quantum correlation

Abstract: Promoting the sensitivity of mid-infrared (MIR) spectroscopy to the single-photon level is a critical need for investigating photosensitive biological samples and chemical reactions. MIR spectroscopy based on frequency upconversion is a compelling pioneer allowing high-efficiency MIR spectral measurement with well-developed single-photon detectors, which overcomes the main limitations of high thermal noise of current MIR detectors. However, noise from other nonlinear processes caused by strong pump fields hind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The time-stretched coincidence spectrum is averaged over a total measurement time of 30 min. In comparison to the previous demonstration (34), the suggested scheme is able to reduce overall exposure time notablely, in the case of illuminating samples with these low magnitudes of MIR photon flux. The time-tagged time-resolved mode of the TCSPC can record individual photon events with their arrival time in all the channels.…”
Section: The Term Of K ′′mentioning
confidence: 80%
See 1 more Smart Citation
“…The time-stretched coincidence spectrum is averaged over a total measurement time of 30 min. In comparison to the previous demonstration (34), the suggested scheme is able to reduce overall exposure time notablely, in the case of illuminating samples with these low magnitudes of MIR photon flux. The time-tagged time-resolved mode of the TCSPC can record individual photon events with their arrival time in all the channels.…”
Section: The Term Of K ′′mentioning
confidence: 80%
“…SPDC photon pairs are used to achieve nonlocal spectral measurement (32,33), effectively suppressing the noise uncorrelated to the upconverted MIR photons. On the basis of the notions of nondegenerate temporal-spectral correlation, broadband MIR upconversion spectroscopy with MIR probe intensities as low as 0.09 photons per pulse has been demonstrated previously (34). Nevertheless, spectrometers/monochromators or interferometers are required for all of the aforementioned MIR spectroscopy investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to its partner in NIR band, quantum light sources in the MIR region can also be generated by using spontaneously parametric processes (SPDCs) in a nonlinear crystal (26)(27)(28). Recently, there are some works about the generation and detection of MIR photon sources theoretically and experimentally (29)(30)(31), and the demonstration of quantum interference and entanglement (32). However, because of the limitations of optical devices and detector performance, research related to the generation of entanglement and photon interference in MIR band has progressed slowly in the past years.…”
Section: Introductionmentioning
confidence: 99%
“…Mancinelli et al ( 29 ) reported on the coincidence measurement of correlated MIR photons at room temperature by using the spectral translation technology to reduce the influence of ambient Planck radiation. Cai et al ( 31 ) reported on the generation of the nondegenerated correlated photon pairs using a short-pulse pump, and the signal photon between 3100 and 3800 nm was upconverted to NIR to detect. Both works above just showed that the strong time correlation between the upconverted photons can notably reduce the noise, but there is no any report on the demonstration of entanglement or nonclassical correlation between photons.…”
Section: Introductionmentioning
confidence: 99%
“…[17] So far, there have been various approaches to implement the involved frequency transduction step. One common way is based on frequency upconversion of the MIR photons through a high-efficiency and low-noise parametric nonlinear conversion, which allows for demonstrating broadband MIR spectrometers at single-photon sensitivity [18][19][20][21] or kHz-above frame rates. [13,22,23] Another promising approach resorts to quantum interferometry of spectrally-entangled photons from spontaneous parametric down conversion (SPDC), [24,25] which features intrinsic single-photon-level sensitivity.…”
Section: Introductionmentioning
confidence: 99%